Mode of Presentation and Associated Autoimmune Diseases in Children with Autoimmune Hepatitis - Nelgin Gerenli; Coşkun Çeltik (Genel Tıp Dergisi)
Background and Aims: Autoimmune hepatiti (AIH) is an inflammatory disease of the liver with variable clinical presentations. 20-40% of the patients with AIH had another associated autoimmune or autoinflammatory disease. This study aimed to assess mode of presentation, biochemical features and outcomes in children with AIH, as well as to evaluate the frequency of concomitant autoimmune diseases (CAIDs). Materials and Methods: 17 children, aged 6 to 18 years were enrolled. The mode of presentation and accompanying autoimmune diseases were recorded. Biochemical parameters as well as immunoglobulin G levels were evaluated either at time of submission and thereafter. Results: Fourteen patients had type-1AIH (10 females, 4 males), and three (2 males, 1 female) had type-2AIH. The mode of presentation was acute in 53% and incidental enzyme elevation in 47% of them. There was an associated autoimmune or auto-inflammatory disease in 35% of the patients, 12% had vitiligo, 6% had celiac disease, 6% had juvenile idiopathic arthritis, 6% had Familial Mediterranean Fever, and one patient had both type-1diabetes mellitus and Hashimoto thyroiditis (HT). The subjects with CAIDs were females (6 patients) with insidious type of presentation. Autoimmune diseases were observed in 24% of the parents (3 had HT, 2 had vitiligo). Conclusion: AIH is a rare but important cause of chronic liver disease in children. Frequent association with autoimmune diseases should be kept in mind as the clinical expression of the associated disease can be extremely variable therefore diagnosis and treatment delay may occur.